MIX E POSIÇÃO DE MATERIAL REFLETOR COLORIDO EM BANCADA DE CULTIVO AMPLIAM ÁREA FOLIAR DA ALFACE - Freitas Souza , Iasmin; Costa , Edilson; Dias Santana , Tamiris; Pacheco de Almeida Prado Bortolheiro , Fernanda; ferreira da Silva Binotti , Flávio; Pradi Vendruscolo, Eduardo (ANAIS DO ENIC, 2026)
-